Assessing underlying effects on the choices of adaptive behaviours in offices through an interdisciplinary framework. (15th August 2020) - Bavaresco, Mateus V.; D'Oca, Simona; Ghisi, Enedir; Pisello, Anna Laura
Abstract: This study evaluates subjective aspects related to the control of building systems (HVAC thermostat, windows, lights, and shades/blinds) in offices. The evaluation is based on a new interdisciplinary framework that combines insights from building physics and social science theories, synthesised in a novel survey. A case study in Florianópolis, southern Brazil, was conducted with 278 valid answers achieved. The levels of intention, ease, attitudes and expectations to share the HVAC thermostat control, as well as knowledge for doing so, were the lowest compared to the other systems evaluated. Additionally, the framework was used to perform a theoretical-driven Structural Equation Modelling (SEM) approach and identify underlying effects on choices of adaptive behaviours in offices. From the SEM results, the major constructs related to adaptive behaviours were determined. Intention and perceived behavioural control (PBC) were deemed positive with significant effects on choices for adaptive behaviours related to HVAC control, windows and shades/blinds. The conceptual model did not show a significant relation of intention and PBC on the lighting system adjustments. This outcome allows us to evaluate further theories, considering that habits may play a role in this context. The results provide important information related to the user-centric control of buildings, as well as support theory-driven interventions to improve adaptive opportunities for occupants. In other words, if one aims to increase adaptive opportunities for occupants, the results of this study suggest subjective aspects that may be enhanced in regards to each building system. Highlights: A survey was used to identify the underlying effects on occupant adaptive behaviours. An interdisciplinary framework enabled theoretical-driven Structural Equation Modelling. Occupants found difficult to share the control of HVAC compared to other building systems. Gender played a role in the intention and expectation of sharing control over the HVAC. Interventions based on social science theories are proposed to boost user adaptations.